Language and Nature in Southern and Eastern Arabia - Al-Ghanim, Kaltham; Watson, Janet C.E. (European Journal of Multidisciplinary Studies, 2021)
This paper examines the relationship between language and nature in southern and eastern Arabia. The work is the result of a two-year interdisciplinary network between the University of Leeds and Qatar University, with partners in the UK, Oman, Canada, the United States, and Russia. Our hypothesis is that local languages and ecosystems enjoy a symbiotic relationship, and that the demise of local ecosystems will adversely affect local languages. In this paper, we examine some of the language–nature effects in Qatar and Dhofar, southern Oman. Our regions differ in that Qatar has two seasons, summer and winter, and is predominantly arid, with occasional rain, while Dhofar together with al-Mahrah in eastern Yemen has four distinct seasons, receiving the monsoon rains between June and September, and, as a result, is home to hundreds of plants and animals found nowhere else in the world. Since the 1970s, in particular, both regions have experienced some of the most rapid socio-economic changes in the world. We ask what affect this socio-economic change has had on the language–nature relationship, and suggest that decoupling of the human–nature relationship as a result of socio-economic change is contributing in these regions to language attrition. We consider spatial terminology, traditional terminology for weather, the traditional measurement of time by narratives around key climatic events, and the role of stars in determining the weather and their role in folklore.
Keywords: Arabic, Qatar, Modern South Arabian, Dhofar, nature, weather, time, climatic events, stars, spatial reference